Tutorials: Transforming Student Learning and Generating Employment - Negi, Mary Ann (Future Science / FSH-PH Publications, 2020)
Tutorials provide quality learning and as a result empowered stu-dents. Teaching in a government university in Zambia, it is recognized like everywhere else in the world, there are large student numbers that flock universities each year with the idea of enhancing their qual-ifications for gainful employment and thereby achieve good lifestyles. However, the gap between learning and achievement is skewed. Many depend on minimal information sufficient enough to pass an examination. It has been observed that students will benefit greatly if there were tutorial hours set aside each day for students to consult, improve their knowledge, acquire confidence and gain a level of pro-fessionalism through student-student and student-teacher interac-tions and activities. Tutorial teaching is a method delivered following a lecture. In a tutorial the teaching is given to a specific group of stu-dents who have feel they need the added impetus to achieve their in-dividual academic goals. The very aim of a tutorial is to help students to improve their academic abilities which are not explicated in a class-room with achievers and overachievers. Tutoring usually help strengthen subject comprehension, boost confidence, and build im-portant learning skills. Tutoring gives students more attention than in a lecture theatre where any special attention which is well-nigh im-possible for the lecturer, if one takes into consideration the limita-tions of time and the number of students in attendance. Tutori-als help students who struggle to keep up with the rest, as well as those who are not challenged enough.